The Effect of Mobile Banking Service Quality And Availability Of Automated Teller Machines (ATM) on Customer Satisfaction of Bank Syariah Indonesia Teluk Kuantan Branch Office - Caflye, Rani; Meliza, Dian; Mulyadita, Redian; Yuliani, Meri; Firdaus, Nil (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Background: This study is motivated by issues and phenomena that occur at BSI KCP Teluk Kuantan, namely: Mobile Banking services that are still experiencing disruptions and the minimal number of BSI ATMs, which is the only one in Kuantan Singingi district.Purpose : This study aims to determine the effect of the quality of mobile banking services and the availability of ATMs on customer satisfaction at BSI KCP Teluk Kuantan.Method : This study uses a mix method research type (combination method), namely qualitative and quantitative. The sampling technique uses the Slovin formula. The population in this study were BSI KCP Teluk Kuantan customers totaling 12,873 people, with a sample size of 44 people. And the data collection techniques used were Observation, questionnaires, interviews, and documentation. The data analysis technique used was descriptive analysis technique.Result : The results of this study can be concluded that: 1) The quality of BSI KCP Teluk Kuantan mobile banking services is very good. 2) The availability of BSI KCP Teluk Kuantan ATMs is still minimal. 3) The variable of mobile banking service quality does not have a significant effect on customer satisfaction, with the T test value showing a sign value of 0.100>0.05. 4) The ATM variable has a significant effect on BSI KCP Teluk Kuantan customer satisfaction, with the T test value (Partial) showing a sign value of 0.002<0.05. Then based on the F test (Simultaneous) the variables of mobile banking and ATM service quality together have an effect on customer satisfaction with a value of 20.586>3.23